Pengaruh Harga Terhadap Keputusan Pembelian dengan Minat Beli sebagai Variabel Intervening di Sate Kambing Muda Mas HJT Surakarta - Annasya Al Sadhilla; Esti Dwi Rahmawati; Indra Hastuti (Jurnal Manajemen Bisnis Era Digital, 2024)
This study aims to analyze the mediation of purchase interest on the influence of price and on purchasing decisions at Sate Kambing Muda Mas HJT Surakarta. This study uses a primary data collection method, namely by distributing questionnaires where the population in this study were customers of Sate Kambing Muda Mas HJT. Sampling in this study used the accidental sampling technique or happened to meet respondents with a sample of 100. The analysis technique used was Structural Equation Modeling-Partial Least Square (SEM-PLS) and used the SmartPLS 4.0 program. The results of this study indicate that price has a positive and significant effect on purchasing decisions, price has a positive and significant effect on purchasing interest, purchasing decisions have a positive and significant effect on purchasing interest, purchasing interest is able to mediate the effect of price on purchasing decisions.